Multiple-Case Studies of Hand-on Breast Massage Techniques used by Breastfeeding Experts - Hyunsoon Park; Insook Cho; Min Kyeong Kim (Korean Society of Women Health Nursing, 2017)
PURPOSE: The aim of this study was to understand the hand-on breast massage techniques used by well-known experts in breastfeeding clinics. METHODS: A qualitative multiple-case design was applied that involved a feasibility test. Four experts sampling qualitative data collected by observing participants and in individual interviews were analyzed by content analysis, linking data to the propositions, and cross-case pattern matching. This study explored differences within and between cases, and the possibilities of replicating findings across cases. Thirty-nine postpartum women participated voluntarily in the feasibility test, which investigated the usability of four massage techniques. RESULTS: The four techniques showed considerable similarities in terms of the application of stimulation to the breast base and increased flexibility of the wired flexible body, which was the core mechanism underlying the techniques. The breast management strategies were consistent with existing practice guidelines with the exception of using cold cabbage to control engorgement pain. There was insufficient scientific evidence for supporting the massage techniques used by the experts. All of the techniques showed 100% education completeness, but application rates were higher for self-control-oriented techniques. CONCLUSION: The massage techniques applied by experts in breastfeeding were based on hypotheses and self-control techniques are feasible to apply in practice.